Personal carbon monoxide exposure, respiratory symptoms, and the potentially modifying roles of sex and HIV infection in rural Uganda: a cohort study - Crystal M. North; Piers MacNaughton; Peggy S. Lai; Jose Vallarino; Samson Okello; Bernard Kakuhikire; Alexander C. Tsai; Marcia C. Castro; Mark J. Siedner; Joseph G. Allen; David C. Christiani (BMC, 2019)
Abstract Background Most of the global burden of pollution-related morbidity and mortality is believed to occur in resource-limited settings, where HIV serostatus and sex may influence the relationship between air pollution exposure and respiratory morbidity. The lack of air quality monitoring networks in these settings limits progress in measuring global disparities in pollution-related health. Personal carbon monoxide monitoring may identify sub-populations at heightened risk for air pollution-associated respiratory morbidity in regions of the world where the financial cost of air quality monitoring networks is prohibitive. Methods From September 2015 through May 2017, we measured 48-h ambulatory carbon monoxide (CO) exposure in a longitudinal cohort of HIV-infected and uninfected adults in rural southwestern Uganda. We fit generalized mixed effects models to identify correlates of CO exposure exceeding international air quality thresholds, quantify the relationship between CO exposure and respiratory symptoms, and explore potential effect modification by sex and HIV serostatus. Results Two hundred and sixty study participants completed 419 sampling periods. Personal CO exposure exceeded international thresholds for 50 (19%) participants. In covariate-adjusted models, living in a home where charcoal was the main cooking fuel was associated with CO exposure exceeding international thresholds (adjusted odds ratio [AOR] 11.3, 95% confidence interval [95%CI] 4.7-27.4). In sex-stratified models, higher CO exposure was associated with increased odds of respiratory symptoms among women (AOR 3.3, 95%CI 1.1-10.0) but not men (AOR 1.3, 95%CI 0.4-4.4). In HIV-stratified models, higher CO exposure was associated with increased odds of respiratory symptoms among HIV-infected (AOR 2.5, 95%CI 1.01-6.0) but not HIV-uninfected (AOR 1.4, 95%CI 0.1-14.4) participants. Conclusions In a cohort in rural Uganda, personal CO exposure frequently exceeded international thresholds, correlated with biomass exposure, and was associated with respiratory symptoms among women and people living with HIV. Our results provide support for the use of ambulatory CO monitoring as a low-cost, feasible method to identify subgroups with heightened vulnerability to pollution-related respiratory morbidity in resource-limited settings and identify subgroups that may have increased susceptibility to pollution-associated respiratory morbidity.